Exploratory Study of the Frequency of Detection and Tissue Distribution of Porcine Circovirus 3 (PCV-3) in Pig Fetuses at Different Gestational Ages - Albert Ruiz; Viviane Saporiti; Eva Huerta; Mònica Balasch; Joaquim Segalés; Marina Sibila (Pathogens, 2022)
Porcine circovirus 3 (PCV-3) has been associated with several pig diseases. Despite the pathogenicity of this virus has not been completely clarified, reproductive disorders are consistently associated with its infection. The aim of the present work was to analyze the presence of PCV-3 DNA in tissues from pig fetuses from different gestational timepoints. The fetuses were obtained either from farms with no reproductive problems (NRP, n = 249; all of them from the last third of gestation) or from a slaughterhouse (S, n = 51; 49 of the second-third of gestation and 2 from the third one). Tissues collected included brain, heart, lung, kidney, and/or spleen. Overall, the frequency of detection of PCV-3 was significantly higher in fetuses from the last third of the gestation (69/251, 27.5%) when compared to those from the second-third (5/49, 10.2%), although the viral loads were not significantly different. Moreover, the frequency of detection in NRP fetuses (69/249, 27.7%) was significantly higher than in S ones (5/51, 9.8%). Furthermore, PCV-3 DNA was detected in all tissue types analyzed. In conclusion, the present study demonstrates a higher frequency of PCV-3 DNA detection in fetuses from late periods of the gestation and highlights wide organ distributions of the virus in pig fetuses.